A comparative test of cream separators - Goodyear, Ellsworth Paul (My University, 1903)
Introduction: Owing to the large number of inquiries received by the Dairy Department of this College in regard to the relative merits of the different makes of separators, Prof. Ed H. Webster planned for a comparative test of a few of the leading makes of machines for the purpose of collecting data for the publication of a bulletin. Although it is not the intention of the Department at the present to publish these results owing to the resignation of Professor Webster which left the Dairy Department without a head, still the work was done with the most exact carefullness although in one or two respects it was not as complete as had at first been planned. PLAN OF THE TESTS: Six different makes of machines all having nearly the same capacity were kindly loaned by the different manufacturers. The attempt was made to secure machines that were the most used throughout the State but in one or two instances the machines could not be secured. The machines used throughout the test and their capacity per hour were, DeLaval, "Alpha"Baby No.1, 450 pounds; Sharpless Tubular, No.4,500 pounds; National, No. 6, 500 pounds; Empire, No. 2, 400-460 pounds; United States, No. 6, 400-450 pounds; and the Iowa Dairy 450 pounds. The work was commenced the 21st of January, 1903 and continued until the 6th of April, 1903. The test was under the supervision of Professor Webster, who assisted in the laboratory at the beginning, and was worked out by E. W. McCrone and the writer (except the power test which was in charge of the Department of Electrical Engineering.) The machines were run under four different conditions including the power test. In the first test the conditions were as nearly ideal as possible according to the directions given by the different manufacturers. In the second the speed was decreased everything else being the same as in number one. In the third cold milk was used, and fourth the amount of power required to run the machines was measured.
Citation: Goodyear, Ellsworth Paul. A comparative test of cream separators. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Mechanical Engineering; Dairy; Cream Separators; Testing; Dairy Department; Theses